Effects of granulocyte-macrophage colony-stimulating factor and foreign helper protein as immunologic adjuvants on the T-cell response to vaccination with tyrosinase peptides - Scheibenbogen, Carmen; Schadendorf, Dirk (International journal of cancer, 2003)
Immunologic adjuvants are used to augment the immunogenicity of MHC class I-restricted peptide vaccines, but this effect has rarely been systematically evaluated in a clinical trial. We have investigated, in a phase I study, whether addition of the 2 adjuvants GM-CSF and KLH can enhance the T-cell response to MHC class I peptide vaccines. Forty-three high-risk melanoma patients who were clinically free of disease received 6 vaccinations with MHC class I-restricted tyrosinase peptides alone, with either GM-CSF or KLH or with a combination of both adjuvants. The primary end point was induction of tyrosinase-specific T cells, and serial T-cell monitoring was performed in unstimulated peripheral blood samples before and after the second, fourth and sixth vaccinations by ELISPOT assay. Tyrosinase-specific IFN-γ-producing T cells were detected as early as 2 weeks after the second vaccination in 5 of 9 patients vaccinated with tyrosinase peptides in combination with GM-CSF and KLH but not in any patient vaccinated with tyrosinase peptides without adjuvants or in combination with either adjuvant alone. After 6 vaccinations, tyrosinase-specific T cells were found in patients immunized with peptides either without adjuvants (3 of 9 patients) or in combination with the single adjuvant GM-CSF (4 of 9 patients) but not with KLH (0 of 10 patients). Our results suggest that addition of either GM-CSF or KLH as a single adjuvant has little impact on the immunogenicity of tyrosinase peptides. The combined application of GM-CSF and KLH was associated with early induction of T-cell responses.